Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Sabun Cuci Piring Organik di Desa Budi Lestari, Tanjung Bintang, Lampung Selatan - Dermawan, Oki; Mustaqim, Fadli Fauzan; Intan, Vara Aptia; Hartini, Entin Tri (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The aim of this community service activity is to use natural ingredients such as pandan leaves, suji leaves and lime as ingredients for making organic dish soap for the people of Budi Lestari Village. The method used is ABCD, training held by the KKN 232 Group with 40 women training participants. With this training, the people of Budi Lestari Village, especially the women's group, can broaden their knowledge about making dishwashing liquid soap. Furthermore, this activity can be used as an additional activity for the community, where so far the community has been less productive in carrying out economically valuable activities so that it is hoped that entrepreneurial motivation will arise in the community and be able to create an independent and innovative village or village community with all the available resources